Production of Hydrogen from Poly Ethylene Terephthalate (PET) using CT 434 ZSM-5 Catalyst at Considerably Low Temperatures - El-Sinawi, A. H. (Engineering, Technology & Applied Science Research, 2016)
The production of hydrogen from Poly Ethylene Terephthalate (PET) using CT 434 ZSM-5 is investigated in this research study. Gas chromatography equipped with a thermal conductivity detector is used to detect the amount of hydrogen produced at different temperatures. The Chromatograph spectrum of pure hydrogen as well as the spectra of evolved gases at 250oC, 280oC, 310oC and 340oC are obtained to validate the presence of hydrogen. The spectra of percentage of hydrogen and peak area to height ratio with increasing temperature shows a similar trend except at the temperature of 340oC. Maximum hydrogen percentage of 20.11% is found in the evolved gases collected at temperature of 250oC. The retention time of sample collected at 340oC is very close to reference retention time 2.014 min observed for a pure hydrogen sample.